Do managers listen to the market? - Kau, James B.; Linck, James S.; Rubin, Paul H. (Journal of Corporate Finance, 2008)
There are competing theories as to whether managers learn from stock prices. Dye and Sridhar (2002), for example, argue that capital markets can be better informed than the firm itself, while Roll [Roll, R., 1986, “The hubris hypothesis of corporate takeovers,” Journal of Business 59, 97–216.] argues managers may ignore market signals due to hubris. In this paper, we examine whether managers listen to the market in making major corporate investments, and whether agency costs and corporate governance mechanisms help explain managers' propensity to listen. We find that, on average, managers listen to the market: they are more likely to cancel investments when the market reacts unfavorably to the related announcement. Further, we find mixed evidence consistent with the notion that managers' propensity to listen is related to agency costs. We find that firms tend to listen to the market more when more of their shares are held by large blockholders, and when their CEOs have higher pay-performance sensitivities.